Development of Degradable Polymers with Controlled Degradation and Applications to Transient Organic Solar Cells - Jin, Hyunjung; Kim, Kyeongmin; Kim, Kyuyeon; Shin, Eul-Yong; Baek, Se-Woong; Park, Sungmin; Son, Hae Jung (AMER CHEMICAL SOC, 2024)
To achieve an organic transient electronic device, the active layer of materials essentially requires the ability to degrade. Furthermore, this degradable material should be controllable such that its degradation can be initiated as required. However, there have been limited studies on controlling the degradation and degradation rate of materials. In this work, we have demonstrated a degradable OPV device by developing a series of degradable polymers interconnected by an imine group via in situ polymerization in a film state. When the degradable polymer is formed in the blend films of conjugated molecules, the blend film exhibits a suitable blend morphology for OPV devices, showing a PCE of 5.05% comparable to that of a control device. Moreover, the degradable polymer substituted at the para position, PYp, shows a clearly faster degradation compared with the polymer substituted at the meta position, PYm. This degradation rate difference originated from the packing structure of the polymers. The PYm polymer forms a more folded and aggregated polymer chain compared with a linear PYp polymer, hindering the acid molecule approach which can cleave the bonds. Furthermore, the degradation rate was fairly suppressed in the PYt polymer connecting three directions in the meta position. Hereby, we show that the degradation rate can be controlled by engineering the numbers and structural positions of bonding arms in amine linkers. We also demonstrated a transient OPV device on a cellulose substrate utilizing an active layer on a degradable polymer base. This research may provide a guideline for designing devices and materials for organic transient electronics.